The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1093/intimm/12.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Inducible differentiation and apoptosis of the pre-B cell receptor-positive pre-B cell line

Abstract: The function of the pre-B cell receptor (pre-BCR) during B cell differentiation is not precisely defined. To investigate the pre-BCR receptor activity, we have established pre-BCR-positive pre-B cell lines that are able to differentiate into immature B cells in vitro. Antibody cross-linking of the pre-BCR induced apoptosis and differentiation accompanied with tyrosine phosphorylation. A specific tyrosine-phosphorylated 43 kDa protein (p43) was found down-stream of the pre-BCR. The results demonstrated the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…We and others have found distinct calcium mobilization profiles upon aggregation of the pre-BCR, contrasting its downstream effects with those of the BCR (35,76,82,83). Unique proteins have also been detected following pre-BCR signaling, but have yet to be characterized (70). All of these data point to particular signaling functions of this receptor that contribute specifically to development.…”
Section: Discussionmentioning
confidence: 75%
“…We and others have found distinct calcium mobilization profiles upon aggregation of the pre-BCR, contrasting its downstream effects with those of the BCR (35,76,82,83). Unique proteins have also been detected following pre-BCR signaling, but have yet to be characterized (70). All of these data point to particular signaling functions of this receptor that contribute specifically to development.…”
Section: Discussionmentioning
confidence: 75%
“…Previously, we revealed that Ab cross-linking of the pre-BCR on the PreBR cell-line induced apoptosis and differentiation accompanied with tyrosine phosphorylation (35), while the immature B cell line, WEHI231, also undergoes apoptosis upon BCR crosslinking (40). Although PreBR cells express low and WEHI231 cells express high , the expression levels of Fc␥RIIB on both cell lines are equal.…”
Section: Discussionmentioning
confidence: 96%
“…PreBR and Fc␥ Ϫ/Ϫ PreBR cell lines were established from pro-B cells in the presence of IL-7 after removal of ST2 as described previously (35). These cell lines were cultured in SF-03 medium (Sanko Jyunyaku, Tokyo, Japan) containing 5 ϫ 10 Ϫ5 M 2-ME, 1ϫ nonessential amino acid solution (Life Technologies, Gaithersburg, MD), 0.03% primatone (Quest International, Naarden, The Netherlands), 2% FCS, and 100 U/ml rIL-7 (36) (a gift of Dr. Sudoh, Toray, Kamakura, Japan), as described previously (14).…”
Section: Animals and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations